2006
DOI: 10.1002/chin.200634151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti‐HIV‐1 and anti‐HCMV Activity of 1‐Substituted 3‐(3,5‐Dimethylbenzyl)uracil Derivatives.

Abstract: 3-(3,5-Dimethylbenzyl)uracil (3) was treated with alkyl halides in the presence of alkali to give 1-substituted congeners. Condensation of 3 with alcohols using the Mitsunobu reaction was also employed as an alternative method. The anti-HIV-1 activity of 1-substituted analogues of 3-(3,5-dimethylbenzyl)uracil was evaluated according to previously established procedures. It appeared that the nitrogen of the 1-cyanomethyl group is important for anti-HIV-1 activity, suggesting interaction with the amino acid resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Then, compound 1 was treated with benzyl bromide to give the corresponding 1-benzylated congeners ( 2 ) in 55% yield as previously reported by Ichikawa et al [10]. This result indicates that the electron-withdrawing chlorine atom facilitates the dissociation of N 1 -H to produce an intermediary uracil-1-anion [7]. Compound 2 was condensed with 3,5-dimethylbenzyl alcohol using the Mitsunobu reaction [11] to afford 3-(3,5-dimethylbenzyl) congener ( 3a ).…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…Then, compound 1 was treated with benzyl bromide to give the corresponding 1-benzylated congeners ( 2 ) in 55% yield as previously reported by Ichikawa et al [10]. This result indicates that the electron-withdrawing chlorine atom facilitates the dissociation of N 1 -H to produce an intermediary uracil-1-anion [7]. Compound 2 was condensed with 3,5-dimethylbenzyl alcohol using the Mitsunobu reaction [11] to afford 3-(3,5-dimethylbenzyl) congener ( 3a ).…”
Section: Methodsmentioning
confidence: 63%
“…Based on the estimation that the hydrogen bond accepting nitrogen of the cyanomethyl group might be related to the strong anti-HIV-1 activity, the introduction of 2-picolyl group or 4-picolyl group at N 1 -position of the uracil analogue has been investigated and resulted in further elevation of anti-HIV-1 activity. These results were confirmed by a computing science method, in which the docking energy of a substrate on HIV-1 RT has been calculated [7].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, we have actively investigated the development of an anti-HIV-1 agent using the structure-activity relationship (SAR) studies of 1,3-disubstituted and 1,3,6-trisubstituted uracils. [12][13][14][15] We have demonstrated that the 3,5-dimethylbenzyl group at the 3-position of the uracil skeleton plays an important role in the enhancement of anti-HIV-1 activity; notably, substitution at the 1-position (e.g. with a benzyl, cyanomethyl, or 4-picolyl group) of 3- (3,5dimethylbenzyl)uracil to obtain 1a-c resulted in good antiviral activity against HIV-1.…”
Section: Introductionmentioning
confidence: 97%
“…We also continued the search for an anti-HIV-1 agent using the structure–activity relationships of the 1,3-disubstituted and 1,3,6-trisubstituted uracils. 1116 We have demonstrated that the 3,5-dimethylbenzyl group at the N 3 -position and the amino group at the C6-position of the uracil skeleton play an important role in enhancing the anti-HIV-1 activity. Notably, substitution at the 1-position (with a benzyl or 4-picolyl group) of 6-amino-3-(3,5-dimethylbenzyl)uracil to obtain 1a–b (Table 1) yielded satisfactory anti-HIV-1 activity, with EC 50 values of 0.07 ± 0.01 µM and 0.03 ± 0.03 µM, respectively.…”
Section: Introductionmentioning
confidence: 99%